PEGARUH LABA RUGI, DEBT PROPORTION, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG DENGAN UKURAN PERUSAHAAN DAN KOMPLEKSITAS OPERASI SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Perbankan Dan Lembaga Keuangan Yang Terdaftar Di Bursa Efek Indonesia 2013 - 2014) - Reza Mardi Putra; Ria Nelly Sari; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to analyze theInfluence of Income, Debt Proportion,and Audit Opinion, on the Audit Report Lag with Company Size and Operation Complexity as Moderating Variable In Banking and Financial Institutionslisted on the Indonesia Stock Exchange(IDX). The sample consists of 82 financial companies that report their financial statement to BAPEPAM in the period of 2013-2014. The sample of this study was determined by purposive sampling method and secondary data then used.Statistical method used to test the research hypothesis is SPSS version 22.00 as the software for processing the data. The result prove that Income, Debt Proportion,and Audit Opinion,positively affect the Audit Report Lag. The result also prove thatCompany Size and Operation Complexitystrengthen the effect of Income, Debt Proportion,and Audit Opinion, on the Audit Report Lag.This is evidenced by the significant value of 0.000 <0.05. The value of Adjusted R Square of 0.243. All of the independent variables jointly influence dependent variables as much as 24.3%, while 75.7% is influenced by other unclear variable.Keyword: Income, Debt Proportion, Audit Opinion, Audit Report Lag